Novel LED-based radiation source and its application in diffuse reflectometry and polarization measurements. Issue 1 (January 2022) - Santourian, I; Quast, T; Teichert, S; Hauer, K-O; Schirmacher, A
Abstract: An LED sphere radiator (LED-SR) was constructed to improve the accuracy in spectral radiance factor measurements performed with the robot-based gonioreflectometer at PTB. Its properties with respect to the spectral range and coverage, the temporal stability, and the homogeneity of the radiation field are presented. Two types of matte ceramic reflection standards were used for spectral radiance factor validation measurements comparing the standardly used halogen sphere radiator (Halogen-SR) and the LED-SR. Due to its designed spectral range at the border between the visible and the UV-A spectral range, the LED-SR is well suited for many applications in diffuse reflectometry. Its use for absolute radiance factor measurements and investigations of the fluorescence properties of diffuse reflecting samples is shown. Reliable polarization-resolved measurements at wavelengths below 430 nm could be carried out with PTB's gonioreflectometer for the first time due to the beneficial signal-to-noise ratio of the LED-SR.